2010
DOI: 10.1111/j.1600-6143.2010.03224.x
|View full text |Cite
|
Sign up to set email alerts
|

Biopsy‐Diagnosed Renal Disease in Patients After Transplantation of Other Organs and Tissues

Abstract: Renal function deteriorates in about half of patients undergoing other transplants. We report the results of 105 renal biopsies from 101 nonrenal transplant recipients (bone marrow 14, liver 41, lung 30, heart 20). Biopsy indications were protracted acute renal failure (9%), creatinine increases (83%), heavy proteinuria (22%), or renal insufficiency before re-transplantation (9%). Histological findings other than nonspecific chronic changes, hypertension-related damage, and signs of chronic CNI toxicity includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
64
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 66 publications
2
64
1
2
Order By: Relevance
“…8,11,14,16,18,39,45 We encountered focal segmental glomerulosclerosis in 3 of 14 (21%, patient nos. 6-8) patients with renal biopsy.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…8,11,14,16,18,39,45 We encountered focal segmental glomerulosclerosis in 3 of 14 (21%, patient nos. 6-8) patients with renal biopsy.…”
Section: Discussionmentioning
confidence: 89%
“…8,18,[26][27][28][29][30][31][32][33][34][35][36][37] In studies also examining nonglomerular pathology, kidney specimens also show concomitant tubulointerstitial and vascular changes in hematopoietic cell transplant patients. 8,14,16,19,38,39 A few single-center studies of autopsy kidney specimen in the hematopoietic cell transplant population have been reported, including one large study focused primarily on thrombotic microangiopathy. 20,21,38,40 We retrospectively reviewed our single-center experience with renal pathology in specimens from three groups of hematopoietic cell transplant recipients.…”
mentioning
confidence: 99%
“…59 Despite some improvements in overall outcomes, renal dysfunction after BMT remains a significant complication, and regardless of the cause, up to 8% of BMT patients require renal replacement therapy. 84,85 Schwarz et al 86 reported the results of 105 renal biopsies from 101 non-renal transplant recipients including liver, lung, bone marrow and heart. Patients with transplant-associated TMA, regardless of transplant type, had the shortest kidney survival.…”
Section: Role Of Tbi In the Development Of Post-bmt Tmamentioning
confidence: 99%
“…Studies about kidney pathology before and after liver transplant are few and sample sizes are small. [1][2][3][4][5] Chronic kidney disease affects 30% to 50% nonrenal organ transplant recipients and causes increased morbidity and mortality in these patients. [6][7][8] Chronic kidney disease also may occur before liver transplant, possibly because of hepatitis C virus-related kidney disease, cirrhotic glomerulonephritis, immunoglobulin A (IgA) nephropathy caused by liver disease, hypertensionrelated nephropathy, diabetic nephropathy, and other glomerular diseases.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Chronic kidney disease also may occur before liver transplant, possibly because of hepatitis C virus-related kidney disease, cirrhotic glomerulonephritis, immunoglobulin A (IgA) nephropathy caused by liver disease, hypertensionrelated nephropathy, diabetic nephropathy, and other glomerular diseases. [1][2][3][4][5][6][7][8][9][10][11] Kidney injury commonly is attributed to chronic calcineurin inhibitor nephrotoxicity, especially after liver transplant. 3,4,6 However, other studies suggest that kidney impairment may be caused by several interconnected factors.…”
Section: Introductionmentioning
confidence: 99%